MANAJEMEN PENDIDIKAN LINGKUNGAN HIDUP DI KABUPATEN PURWAKARTA MELALUI PROGRAM TATANEN DI BALE ATIKAN - Manpan Drajat (STAI Pelabuhan Ratu, 2022)
The current state of the earth's environment is concerning. There must be systematic efforts in the short and long term to collectively awaken the citizens of the earth. One important effort is through education. Environmental education is an educational material that students must understand as early as possible. Responding to the above problems, the Purwakarta District Education Office adopted a policy by organizing local culture-based environmental education, namely tatanen in bael atikan. This study aims to find out how the implementation of the governance program in the perspective of education management. The method used in this study uses a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation. The results of the study explain that planning is carried out by a team that recruits experts to make policies down to the technical stage, organizing involves all levels of high leadership in the education office to school principals. Likewise, in its implementation, the technical team is commanded by leaders from every level in the education office, also involving students and parents of students. Whereas in terms of supervision is carried out using the existing service structure with instruments that have been prepared in detail.